THE CONTROL OF CHAMBER GEOMETRY ON TRIGGERING VOLCANIC ERUPTIONS - Woods A.W.; Pyle D.M. (My University, 1997)
The pressure evolution of a cooling and crystallising body of magma stored in the crust is sensitive to the depth and vertical extent of the chamber and also to the volatile content of the magma. In shallow sill-like chambers or in chambers containing magma of high volatile content, the magma becomes vapour-saturated on emplacement. The chamber pressure then increases as the melt cools and crystallises owing to the concomitant exsolution of volatile species. This can lead to the eruption of relatively unevolved, crystal-poor magma. In deep sill-like chambers or chambers with low volatile (H2O) contents, the magma remains undersaturated until a significant fraction of the melt has crystallised. While unsaturated, crystallisation leads to a decrease in chamber pressure since the crystals are typically denser than the melt. However, once the magma becomes saturated, vapour bubbles are exsolved, leading to an increase in pressure and possible eruption of a crystal-rich magma, although, at this stage the magma may be so crystalline that it is essentially immobile. In chambers of significant vertical extent, the upper part of the chamber may be saturated and exsolving volatiles while the lower part remains unsaturated. This may cause a decline in pressure during the early stages of crystallisation when the contraction of the undersaturated deeper magma dominates. However, as the saturation surface migrates downwards through the magma, the pressure may build up again, eventually leading to eruption of relatively crystal-rich magma. These results also suggest that inter-eruption time-scales are greater in deeper chambers owing to the greater amount of crystallisation required before eruption. We show that the model is broadly consistent with data from several historical eruptions.
Keywords: MAGMA CHAMBERS; EMPLACEMENT; ERUPTIONS